2020
DOI: 10.3390/hydrology7020020
|View full text |Cite
|
Sign up to set email alerts
|

On the Ability of LIDAR Snow Depth Measurements to Determine or Evaluate the HRU Discretization in a Land Surface Model

Abstract: To find the adequate spatial model discretization scheme, which balances the models capabilities and the demand for representing key features in reality, is a challenging task. It becomes even more challenging in high alpine catchments, where the variability of topography and meteorology over short distances strongly influences the distribution of snow cover, the dominant component in the alpine water cycle. For the high alpine Research Catchment Zugspitze (RCZ) a new method for objective delineation of hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
(105 reference statements)
2
4
0
Order By: Relevance
“…Since 2014, a snow scale was installed at the LWD station, which enabled us to use these measured SWE for more recent years as a good possibility to investigate the precipitation under catch. Similar to the literature reported under catch of snow precipitation of up to 50% (WMO, 2011; Grossi et al, 2017), we also found out in our former study (Weber et al, 2020) that we can expect an under catch of 50% for the RCZ. Assuming that under catch variations in precipitation over the entire catchment are rather negligible, the DWD snow precipitation has been corrected with the factor derived at the LWD station.…”
Section: Interactive Commentsupporting
confidence: 93%
See 2 more Smart Citations
“…Since 2014, a snow scale was installed at the LWD station, which enabled us to use these measured SWE for more recent years as a good possibility to investigate the precipitation under catch. Similar to the literature reported under catch of snow precipitation of up to 50% (WMO, 2011; Grossi et al, 2017), we also found out in our former study (Weber et al, 2020) that we can expect an under catch of 50% for the RCZ. Assuming that under catch variations in precipitation over the entire catchment are rather negligible, the DWD snow precipitation has been corrected with the factor derived at the LWD station.…”
Section: Interactive Commentsupporting
confidence: 93%
“…ever, as we found out in our former study for the RCZ (Weber et al, 2020) and which is also known from other studies (e.g. Grünewald et al 2013), the spatial distribution in various years and also during the most of the season does not change much (except at the very beginning and the very end of the season).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Detailed water balance and karst water discharge studies at the Partnach spring investigated runoff responses to rainfall and snowmelt dynamics and characterised the karst groundwater aquifer (Hürkamp et al, 2019;Morche and Schmidt, 2012;Rappl et al, 2010;Wetzel, 2004). Numerous snow-hydrological studies investigated the spatiotemporal dynamics of snow cover and the snow water equivalent (SWE; Bernhardt et al, 2018), combining monitoring techniques, such as terrestrial photogrammetry (Härer et al, 2013(Härer et al, , 2016, remote sensing (Härer et al, 2018) or lidar observations (Weber et al, 2016(Weber et al, , 2020(Weber et al, , 2021 with different complex snow-hydrological modelling. Some limitations arising from these studies were the small number of cloudfree remote sensing scenes in the visible and near-infrared spectrum to derive spatially distributed snow cover maps at high temporal resolutions and the limited spatial extent of the terrestrial photogrammetry and lidar observations in the RCZ (Härer et al, 2016;Weber et al, 2016Weber et al, , 2020.…”
mentioning
confidence: 99%
“…Both photogrammetry and lidar observation techniques are only capable of measuring snow heights, but not hydrologically relevant SWE values, directly and thus rely on additional snow density data from local snow pit or snow weight measurements. While snow cover and snow height data are able to condition the snow-hydrological model behaviour to some degree (Weber et al, 2021), it was recently shown that integral data from satellite (Bahrami et al, 2020) and terrestrial gravimetry (Güntner et al, 2017) providing a footprintaveraged time series of the terrestrial water storage anomaly (TWSA) can greatly improve the identification of water balance components and relevant hydrological processes on catchment scale.…”
mentioning
confidence: 99%